Synthesis and Biological Activity of 2-Methylpiperazine-Dithiocarbamato and Di-(2-Methyl-5-Chloro phenyl) Dithiophosphinato Derivatives of Triorganation(IV) Chloride - Gogoi, P.K.; Phukan, D.P.; Das, D.K. (Asian Journal of Chemistry, 2010)
Complexes of triphenyltin(IV) chloride with 2-methyl-piperazinedithiocarbamate (Na salt, 2-Mepipzdtc) and di-(2-methyl-5-chlorophenyl) diphosphinate (Na salt; MeCldtpi) have been synthesised and characterised by elemental analysis, IR and 1H-NMR studies. Unlike the symmetrical bidentate nature of the dithiocarbamato group an unsymmetrical bidentate ligation is suggested for the dithiophosphinato group towards organotin(IV) moiety. The thermal stability of the compounds, biological activity against E. coli and potential antifungal role of the compounds in wood preservation have been evaluated.